Rivers and Lakes: Zhuangzi’s Critique of Just War and the Zhuangzian War Ethics and Peace Strategy - Ting-mien Lee (Religions)
Just war theory, significantly shaped by Christian moral theology, has provided a prominent ethical framework for discussions on the justice of war. Numerous works have been published on classical Chinese counterparts, including passages from the Mengzi, Mozi, Xunzi, and Huangdi Sijing. Although the Zhuangzi frequently discusses warfare, it has been largely overlooked in this field of research because its war ethics do not revolve around any concept similar to that of justice. Based on Zhuangzian critiques of Confucian and Mohist views on justice, this paper tentatively reconstructs Zhuangzian war ethics. This reconstruction reveals a perspective that the concept of just war or justified war is inherently problematic, and promoting such ideas can be perilous and even morally questionable. The belief that just war theory can help us identify a “just side” to morally condemn or legally restrain aggressors is a dangerous illusion. In practice, this approach fails to prevent wars and often exacerbates conflict. According to the Zhuangzian perspective, during wars, states do not operate as traditional political entities with universal jurisdiction and centralized authority. Instead, they resemble rivers and lakes with indistinct boundaries, rendering the concepts of justice and punishment largely irrelevant. A practical peace strategy, therefore, must abandon the pursuit of administering justice and punishing wrongdoers. Instead, it should focus on strategies that facilitate the involved parties to “forget” their grudges and start their peaceful relationship anew.